School and Community Relations Management at SMAN 1 Parakan and SMAN 1 Temanggung: POAC Analysis - Sri Muryati; Wiwik Wijayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study aimed to: (1) describe the management of school–community relationships at SMAN 1 Parakan and SMAN 1 Temanggung; (2) identify supporting factors in the management of school–community relationships; and (3) identify inhibiting factors affecting the implementation of such relationships in both schools. This study employed a qualitative method with a case study approach. The research was conducted from June to September 2025. The subjects included principals, vice principals for public relations, teachers, school committees, parents or guardians, and community members from SMAN 1 Parakan and SMAN 1 Temanggung. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model consisting of data collection, data reduction, data display, and conclusion drawing. The findings showed that the management of school–community relationships in both schools was implemented through the POAC management functions: planning, organizing, actuating, and controlling. SMAN 1 Parakan demonstrated more optimal relationship management with the community, where community members were actively involved from planning to evaluation stages, creating a cultural-based relationship pattern. In contrast, SMAN 1 Temanggung showed limited direct community involvement but maintained strong collaboration with alumni, resulting in an educative relationship pattern. Supporting factors identified included stakeholder involvement, well-planned programs, school openness to suggestions and feedback, and alumni participation. Meanwhile, inhibiting factors included passive participation of some parents or guardians, differences in available time among stakeholders, limited program funding, and complaints from some community members regarding activities conducted outside operational hours